Discordant and heterogeneous clinically relevant genomic alterations in circulating tumor cells vs plasma DNA from men with metastatic castration resistant prostate cancer. Issue 4 (28th November 2019) - Gupta, Santosh; Hovelson, Daniel H.; Kemeny, Gabor; Halabi, Susan; Foo, Wen‐Chi; Anand, Monika; Somarelli, Jason A.; Tomlins, Scott A.; Antonarakis, Emmanuel S.; Luo, Jun; Dittamore, Ryan V.; George, Daniel J.; et al.
Abstract: Circulating tumor cell (CTC) and cell‐free (cf) DNA‐based genomic alterations are increasingly being used for clinical decision‐making in oncology. However, the concordance and discordance between paired CTC and cfDNA genomic profiles remain largely unknown. We performed comparative genomic hybridization (CGH) on CTCs and cfDNA, and low‐pass whole genome sequencing (lpWGS) on cfDNA to characterize genomic alterations (CNA) and tumor content in two independent prospective studies of 93 men with mCRPC treated with enzalutamide/abiraterone, or radium‐223. Comprehensive analysis of 69 patient CTCs and 72 cfDNA samples from 93 men with mCRPC, including 64 paired samples, identified common concordant gains in FOXA1, AR, and MYC, and losses in BRCA1, PTEN, and RB1 between CTCs and cfDNA. Concordant PTEN loss and discordant BRCA2 gain were associated with significantly worse outcomes in Epic AR‐V7 negative men with mCRPC treated with abiraterone/enzalutamide. We identified and externally validated CTC‐specific genomic alternations that were discordant in paired cfDNA, even in samples with high tumor content. These CTC/cfDNA‐discordant regions included key genomic regulators of lineage plasticity, osteomimicry, and cellular differentiation, including MYCN gain in CTCs (31%) that was rarely detected in cfDNA. CTC MYCN gain was associated with poor clinical outcomes in AR‐V7 negative men and small cell transformation. In conclusion, we demonstrated concordance of multiple genomic alterations across CTC and cfDNA platforms; however, some genomic alterations displayed substantial discordance between CTC DNA and cfDNA despite the use of identical copy number analysis methods, suggesting tumor heterogeneity and divergent evolution associated with poor clinical outcomes.